ANALYSIS OF HEALTH SERVICE SATISFACTION IN OUTPATIENTS AT THE COMMUNITY LUNG HEALTH CENTER IN PRABUMULIH CITY - Merry Iriani; Akhmad Dwi Priyatno; Ali Harokan; Nurul Fitriyah; Lisa Fitri (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Patient satisfaction is the result of good healthcare. One of the goals of improving the quality of health services is to increase patient satisfaction. The purpose of this study was to determine patient satisfaction with outpatient health services at BKPM Prabumulih City in 2025. The research method used is quantitative with a cross-sectional approach which is the population, namely all patients or customers who receive services at BKPM in March 2025. sampling technique with a total population of 40 respondents. The results of the study obtained the pvalue of the age variable pValue = 0.031 OR 4.19, gender pValue = 0.822, education level pValue = 0.009 OR 0.163, Reliability pValue = 0.001 OR 11.900, responsiveness pValue = 0.45, Assurance pValue = 0.381, Empathy pValue = 0.000, Tangible pValue = 0.476. Empathy is a significant predictor of outpatient satisfaction with an OR of 15.750. The conclusion in this study is that there is a significant relationship between age, education level, reliability, and empathy on patient satisfaction and the most dominant variable is empathy. There is no significant relationship between gender, responsiveness, assurance, and tangible to patient satisfaction.